PENDEKATAN SAINTIFIK BERBANTUKAN MEDIA POWER POINT PADA MATERI PROTISTA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMAN 1 BOLA - Sukarman Hadi Jaya Putra (Unika Santu Paulus Ruteng, 2020)
The students learning outcomes on protista material is still below the minimum completeness criteria. This is caused by the lack of application of learning methods and unattractive media. The use of media in learning as a tool to submit the material and create effective and efficient learning activities so as to increase students interest and learning outcomes. The purpose of this study is to increase the motivation and cognitive learning outcomes of students with the scientific approach method assisted by power point media at SMAN 1 Bola. This type of research is a classroom action which consists of two cycles. The type of data in this study are qualitative and quantitative. The results of first cycle obtained the completeness of the learning outcomes test with an average of 79,2% and students activities were in the quite good category of 79,4%. The average completeness of learning outcomes in the second cycle was 85,1%. With reference to the KKM (Keriteria Minimum completeness) which is 75. The conclusion obtained in this study is the application of a scientific approach assisted by power point media can improve the motivation and learning outcomes of students of class X at SMAN 1 Bola